Hadis dan Fenomena Influencer Muslim: Analisis Konten Dakwah Akun Instagram Naisa Alifia Yuriza - Manik, Zulfirman; Alyaziah; Lestari, Dhea; Hasanah, Naila; Hafizah, Zukhriatul (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The phenomenon of digital da’wah by Muslim influencers is a new way to disseminate hadith. This research focuses on the way Naisa Alifia Yuriza, a young Muslim influencer on Instagram, presents hadith-based da’wah content, as well as the forms of hadith mediation that appear in the digital narratives she builds. This research aims to understand the transformation of religious authority and the dynamics of popularity in the practice of da’wah in the social media era. This research aims to analyze the practice of hadith mediation in Naisa Alifia Yuriza’s Instagram preaching content as a representation of non-traditional religious authority in the digital space. This research uses a qualitative method with a content analysis approach to Naisa’s Instagram posts, which contain quotes, paraphrases, or implicit references to hadith. The results of the research show that Naisa conveys hadith values, such as hadiths about Allah’s mercy in covering the disgrace of his servants, being kind to Allah, and seeking the night of Laylat al-Qadr on the last ten nights of Ramadan. These hadith are conveyed through personal stories, popular language, and aesthetic visualizations that emphasize moral and motivational aspects over textual authenticity. This study concludes that Naisa’s da’wah reflects a form of hadith mediation that is adaptive to digital culture, where scholarly authority is negotiated through affective communication and visual appeal. However, this form of mediation still poses several significant challenges regarding the authenticity and legitimacy of the hadith she conveys. Some of Naisa’s uploaded content features quotations from popular hadith without citing their sources or quality status, thus opening up the possibility of using ḍaʻīf hadith or even hadith whose authenticity is disputed. Furthermore, the presentation style is very concise and motivational, potentially obscuring the hadith’s original context.